EFFECT OF FILLER TYPE ON PROPERTIES OF HOT ROLLED ASPHALT MIXTURE - Haeman Wenan, Amadeus
Over the past few years, Hot Rolled Asphalt has been extensively utilised in Indonesia as a wearing course material, because it is very durable, almost completely impermeable and easy to lay and compact. During the past decade the growth of road transport has been so great that the increased utilisation of Hot Rolled Asphalt has resulted in the urgent need for a guide to aid in the selection of materials and asphalt surfacing types. One of the most important characteristics of Hot Rolled Asphalt is that the aggregate is gap graded. It contains very little medium sized aggregate and consists of a matrix of sand, fine mineral filler and bitumen into which coarse aggregate is incorporated. The strength of Hot Rolled Asphalt is not provided by coarse aggregate interlock but is developed in the fine aggregate, mineral filler and bitumen mortar. Portland cement is normally utilised as the mineral filler, but sometimes portland cement is not easily available and the price is relatively expensive as well. This thesis deals with the several types of material that can be utilised as a mineral filler; apart from being easily available, these materials are also cheaper when compared to portland cement. Materials investigated as a mineral filler in Hot Rolled Asphalt mixtures were sulphur, fly ash, hydrated lime and soil dust. Tests carried out to investigate the effect of filler type on the properties of Hot Rolled Asphalt mixtures were the Marshall test which is generally associated with the stability of the mixtures, the Marshall Immersion test which is concerned with the durability of the mixtures due to the effect of water, the Indirect Tensile test which is concerned with the flexibility of the mixtures and the Wheel Tracking test which evaluates the resistance of the mixtures to permanent deformation. The mixture specifications comply with British Standard wearing course type C, having a designation of 30/10, nominal thickness of layer 35 mm and intended to carry heavy traffic. Hydrated lime and fly ash are potential substitute fillers for portland cement, since the results of the investigation show that these materials satisfactorily meet the specified requirements. Hydrated lime may be effectively utilised in cases where the properties of the mix in particular its resistance to the effects of water, require improvement; mixtures containing hydrated lime gave the highest index of retained strength (+ 90%). Soil dust may be utilised in conditions of light to medium traffic. Economic factors should be considered in utilising soil dust as a filler in Hot Rolled Asphalt, since they required higher bitumen content. Utilising sulphur as a substitute filler for portland cement is considered to be too risky, due to the disintegration of the specimens when immersed at a relatively high temperature.